Clinical Efficacy and Safety of Two Cycles of Intra-Articular Injection of Porcine Atelocollagen Versus Hyaluronic Acid in Knee Osteoarthritis - Yong In; Keun Young Choi; Man Soo Kim (Bioengineering, 2025)
(1) Background: Knee osteoarthritis (KOA) induces pain, stiffness, and impaired mobility, particularly in aging populations. Despite providing symptom relief, the long-term efficacy of intra-articular hyaluronic acid (HA) injections remains unclear. With its longer intra-articular residence time and potential chondroprotective effects, porcine-derived atelocollagen is an alternative to HA. We aimed to compare the safety and efficacy of collagen versus HA injections in symptomatic KOA. (2) Methods: This retrospective observational study included 40 patients with KOA who received either two cycles of collagen or HA injections at 6-month intervals. Clinical outcomes were assessed using the visual analog scale (VAS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) at baseline and 6 months after the first and second injections (Cycle 1 and Cycle 2, respectively). Patient satisfaction and adverse events were recorded. Non-inferiority analysis was conducted for VAS and WOMAC score changes. (3) Results: Significant intragroup improvements in VAS and WOMAC scores were noted after each injection cycle (p < 0.05), albeit without significant between-group differences, non-inferiority of collagen to HA based on predefined margins, and comparable patient-reported satisfaction (>85% reported improvement after each cycle), with similar incidence of mild adverse events (collagen: 20%, HA: 25%, p = 0.705). (4) Conclusions: Intra-articular collagen injections were clinically non-inferior to HA in reducing pain and improving function in patients with KOA across two treatment cycles. Given its favorable safety profile and potential structural benefits, collagen may serve as a viable alternative injectable therapy for the non-surgical management of KOA.